Urinary biomonitoring in firefighters: baseline data of polycyclic aromatic hydrocarbons metabolites - Barros, B. (2023)
Polycyclic aromatic hydrocarbons (PAHs) are among the most relevant pollutants in the firefighting context and urine the most straightforward and interesting matrix for biomonitoring. Recent studies have found elevated levels of PAH metabolites in firefighters in comparison to the general population. Since Portuguese firefighters are poorly characterized, the aim of this study was to determine the baseline data (i.e., with no recent exposure to fire emissions) of several urinary monohydroxyl-PAHs (OHPAHs; 1-hydroxynaphthalene, 1-hydroxyacenaphthene, 2-hydroxyfluorene, 1-hydroxyphenanthrene, 1- hydroxypyrene, 3-hydroxybenzo(a)pyrene) in this occupational group. A total of 106 Portuguese firefighters were enrolled in this study and characterized through a previously validated questionnaire. Individual OHPAHs were detected with a frequency of 90-99%, except for 3-hydroxybenzo(a)pyrene (biomarker of exposure to carcinogenic PAHs) that was not identified. The individual levels of 1-hydroxypyrene (the established biomarker for PAHs exposure) were lower than the recommended biological exposure limit proposed by the American Conference of Governmental Industrial Hygienists (0.93 µmol/mol creatinine). This study characterized the baseline data of PAHs exposure in Portuguese firefighters by urinary biomonitoring, which enables comparison with occupational studies from other countries and contributes to fill a research gap in Portugal